PENGARUH PENGGUNAAN SMART TV TERHADAP KOMUNIKASI DAN KOLABORASI SISWA MADRASAH ALIYAH - Ikbar Rasyid; Christian Arief Jaya (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2026)
Two of the four core competencies of the 21st century that students must possess are the ability to communicate and collaborate. However, there has been little in-depth research on the development of these two skills in schools that use learning technologies such as Smart TVs. As stipulated in Presidential Instruction Number 7 of 2025, the national learning digitalization program has encouraged the presence of Smart TVs in educational environments, including at the State Islamic Senior High School (MAN) in Demak Regency. However, the number of studies specifically examining the effect of Smart TV use on students' ability to communicate and collaborate in Islamic educational institutions is still very limited. Thus, the interaction dynamics generated by the characteristics of the madrasah learning culture may be very different. Therefore, this study attempts to explain how Smart TV use impacts students' ability to communicate and collaborate at the State Islamic Senior High School (MAN) in Demak Regency. This study uses a qualitative descriptive approach. Data were collected through active participation, in-depth interviews with four informants from grades XI and XII, and documentation of various classroom learning activities. Next, the collected data were analyzed using an interactive analysis model developed by Miles, Huberman, and Saldana. This model consists of three main stages: data condensation, data presentation, and drawing and verifying conclusions. The results of the study indicate that the use of smart TVs benefits the development of students' communication skills. Seven interrelated thematic concepts reflect these findings: Smart TVs serve as a shared center of attention in the learning process, media increases students' courage to communicate, media functions as a visual scaffold that supports presentation tasks, creates collective accountability based on display targets to be achieved, media operators emerge as new collaborative roles in groups, and the development of collaboration in these groups. These findings indicate that the presence of smart TVs does not automatically change the way students learn in the classroom. On the other hand, planned and organized pedagogical strategies are needed to maximize media collaboration in madrasah education. ABSTRAK Dua dari empat kompetensi inti abad ke-21 yang harus dimiliki siswa adalah kemampuan berkomunikasi dan kolaborasi. Namun, belum banyak penelitian mendalam tentang pengembangan kedua keterampilan ini di sekolah yang menggunakan teknologi pembelajaran seperti Smart TV. Sebagaimana diatur dalam Instruksi Presiden Nomor 7 Tahun 2025, program digitalisasi pembelajaran nasional telah mendorong kehadiran Smart TV di lingkungan pendidikan, termasuk di MAN Kabupaten Demak. Namun, jumlah studi yang secara khusus meneliti pengaruh penggunaan Smart TV terhadap kemampuan siswa untuk berkomunikasi dan berkolaborasi di institusi pendidikan Islam masih sangat terbatas. Dengan demikian, dinamika interaksi yang dihasilkan oleh karakteristik budaya pembelajaran madrasah mungkin sangat berbeda. Oleh karena itu, penelitian ini mencoba menjelaskan bagaimana penggunaan Smart TV berdampak pada kemampuan siswa untuk berkomunikasi dan berkolaborasi di Madrasah Aliyah Negeri (MAN) Kabupaten Demak. Studi ini menggunakan pendekatan deskriptif kualitatif. Data dikumpulkan melalui partisipasi aktif, wawancara mendalam dengan empat informan dari kelas XI dan XII, dan dokumentasi berbagai kegiatan pembelajaran di kelas. Selanjutnya, data yang dikumpulkan dianalisis menggunakan model analisis interaktif yang dikembangkan oleh Miles, Huberman, dan Saldana. Model ini terdiri dari tiga tahap utama: kondensasi data, presentasi data, dan penarikan dan verifikasi kesimpulan. Hasil penelitian menunjukkan bahwa penggunaan Smart TV menguntungkan perkembangan kemampuan komunikasi siswa. Tujuh konsep tematik yang saling terkait mencerminkan temuan ini: Smart TV berfungsi sebagai pusat perhatian bersama dalam proses pembelajaran, media meningkatkan keberanian siswa untuk berkomunikasi, media berfungsi sebagai perancah visual yang mendukung tugas presentasi, menciptakan akuntabilitas kolektif berdasarkan target tampilan yang harus dicapai, operator media muncul sebagai peran kolaboratif baru dalam kelompok, dan pengembangan kolaborasi dia Temuan ini menunjukkan bahwa kehadiran Smart TV tidak secara otomatis mengubah cara siswa belajar di kelas. Di sisi lain, strategi pedagogis yang direncanakan dan terorganisir diperlukan untuk memaksimalkan kolaborasi media dalam pendidikan madrasah.